Videoconference System for Rural Education: Issues, Challenges, and Solutions a Title is Fewest Possible Words - Kusprasapta Mutijarsa; Yoanes Bandung; Luki Bangun Subekti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In this paper, we presented issues, challenges, and solutions of videoconference system for rural education. First, we discussed several issues on the implementation of videoconference system for education, particulary in rural area in Indonesia, which covered videoconference requirement, rural condition, and education needs. Second, we presented several challenges consisted of choosing videoconference technology, choosing compression method, system and application development, ensuring quality of services, and ensuring quality of experiences. Based on the issues and challenges, we proposed a solution of videoconference system which is specifically deployed in rural education. The solution was based on WebRTC technology implemented in Intel i5 core miniPC choosen to increase portability of the system. A STUN server was built on Javascript to facilitate communication between each client terminal. A simple and intuitive user interface was designed to facilitate the use of application by rural people. The system was deployed at two elementary schools in Cianjur, West Java, representing rural education in Indonesia. From the experiment, we obtained video sent data rate 82 kbit/s, video received data rate 245 kbit/s, average delay 316 ms and packet lost rate 1.32%. The experiment results showed that the audio and video quality can be accepted by users to implement distance learning.